The Status of Linguistics as a Science - Sapir, Edward (Acta Universitatis Danubius. Communicatio, 2024)
The long tried methods of Indo-European linguistics have proved themselves by the success with which they have been applied to other fields, for instance Central Algonkian and Athabaskan. An increasing interest in linguistics may be noted among workers in anthropology, culture history, sociology, psychology, and philosophy. For all of them linguistics is o basic importance: its data and methods show better than those of any other discipline dealing with socialized behaviour the possibility of a truly scientific study of society. Linguistics should, on the other hand, become aware of what their science may mean for the interpretation of human conduct in general.